A concise radiosynthesis of the tau radiopharmaceutical, [18F]T807. (24th July 2013) - Shoup, Timothy M.; Yokell, Daniel L.; Rice, Peter A.; Jackson, Raul N.; Livni, Eli; Johnson, Keith A.; Brady, Thomas J.; Vasdev, Neil
<x xml:space="preserve">Abstract</x> Fluorine‐18 labeled 7‐(6‐fluoropyridin‐3‐yl)‐5H‐pyrido[4, 3‐b]indole ([18F]T807) is a potent and selective agent for imaging paired helical filaments of tau and is among the most promising PET radiopharmaceuticals for this target in early clinical trials. The present study reports a simplified one‐step method for the synthesis of [18F]T807 that is broadly applicable for routine clinical production using a GE TRACERlab™ FXFN radiosynthesis module. Key facets of our optimized radiosynthesis include development and use of a more soluble protected precursor, tert‐butyl 7‐(6‐nitropyridin‐3‐yl)‐5H‐pyrido[4, 3‐b]indole‐5‐carboxylate, as well as new HPLC separation conditions that enable a facile one‐step synthesis. During the nucleophilic fluorinating reaction with potassium cryptand [18F]fluoride (K[18F]/K222) in DMSO at 130 °C over 10 min the precursor is concurrently deprotected. Formulated [18F]T807 was prepared in an uncorrected radiochemical yield of 14 ± 3%, with a specific activity of 216 ± 60 GBq/µmol (5837 ± 1621 mCi/µmol) at the end of synthesis (60 min; n = 3) and validated for human use. This methodology offers the advantage of faster synthesis in fewer steps, with simpler automation that we anticipate will facilitate widespread clinical use of [18F]T807. Copyright © 2013 John Wiley & Sons, Ltd.